Ethylenedicysteine Versus Diethylenetriamine Pentaacetic Acid as the Carrier of Technetium Tc 99m in Diuretic Renography for Patients with Upper Urinary Tract Obstruction - Shahrokh, Hossein; Movahhed, Mansour; Zargar Shoshtari, Mohammad Ali; Orafa, Amir Mohammad; Hekmat, Sepideh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: L,L-ethylenedicysteine (EC) is a new carrier of technetium Tc 99m (99mTc) with a lower affinity to plasma albumin in comparison with diethylenetriamine pentaacetic acid (DTPA). We comparedÂ 99mTc-EC scan with 99mTc-DTPA scan in diuretic renography for patients with obstructive uropathy. Materials and Methods: Thirty-three patients with upper urinary tract obstruction were randomly selected and underwent diuretic renographies by 99mTc-EC and 99mTc-DTPA. The counts of radioisotope per pixel in the target (the kidney) and background tissues as well as the clearance half-life of these two radiopharmaceuticals were measured and compared.Â Results: Mean counts of radioisotope per pixel in the target tissue was not different between 99mTc-EC and 99mTc-DTPA scans, but in the background tissue, it was less for 99mTc-EC (P = .003). Target-background ratio was higher for 99mTc-EC scan (3.80 Â± 2.11 versus 2.48 Â± 1.39; P < .001). Renal clearance half-life of radioisotope was shorter for 99mTc-EC scan than 99mTc-DTPA scan (58.15 Â± 15.17 minutes versus 78.65 Â± 19.99 minutes; P = .033). The results were similar for uremic patients (with a serum creatinine level > 2mg/dL). Conclusion: Target-background ratio of radiopharmaceutical uptake rates in diuretic renography was a good indicator of the higher resolution of 99mTc-EC than 99mTc-DTPA scan. We also demonstrated the faster clearance of 99mTc-EC than 99mTc-DTPA. This results in less radiation that is especially useful in children. To our opinion, 99mTc-EC can better depict the kidneys in comparison with 99mTc-DTPA.